Algorithmic prediction of functional changes within protein sequence - Tolar, Nikolas (Jihočeská univerzita, 2021)
The Following thesis provides a theoretical background to the biology of a naked mole-rat (Heterocephalus glaber), highlighting its unique characteristics that could potentially be explained by altered epigenetic mechanisms. In order to identify potentially functional evolutionarily changed sites in epigenetic modifiers, we developed a novel approach to protein scanning through the utilization of multiple-sequence alignments and protein annotations available in public databases. The key result is computer software and analysis of the obtained results, identifying candidate proteins with potentially altered functions.
Algorithmic prediction of functional changes within protein sequence
Keywords: epigenetics; naked mole-rats; bioinformatics; proteins; transcription factors; Python; functional changes; multiple-sequence analysis; epigenetics; naked mole-rats; bioinformatics; proteins; transcription factors; Python; functional changes; multiple-sequence analysis